1984
DOI: 10.1093/ajcn/40.5.1090
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of respiratory disease and diarrhea in children with preexisting mild vitamin A deficiency

Abstract: Preschool-age rural Indonesian children were reexamined every 3 months for 18 months. An average of 3135 children were free of respiratory disease and or diarrhea at the examination initiating each of the six, 3-month follow-up intervals. Children with mild xerophthalmia (night blindness and/or Bitot's spots) at the start and end of an interval developed respiratory disease and diarrhea at twice (p less than 0.001) and three times (p less than 0.001) the rate, respectively, of children with normal eyes during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
158
0
14

Year Published

1986
1986
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 434 publications
(178 citation statements)
references
References 20 publications
2
158
0
14
Order By: Relevance
“…Vitamin A deficiency is widespread in developing countries, particularly in young children and women where it is an important cause of immune function impairment (Semba, 1994) and increased risk of morbidity and mortality from infectious and other diseases (Fawzi et al, 1993;Sommer et al, 1984;West et al, 1999). The main causes of vitamin A deficiency are inadequate intake of vitamin A-rich foods such as liver, full milk, butter, eggs, whole fish, green leafy vegetables and yellow-orange fruits, as well as increased requirements due to a high burden of infectious diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin A deficiency is widespread in developing countries, particularly in young children and women where it is an important cause of immune function impairment (Semba, 1994) and increased risk of morbidity and mortality from infectious and other diseases (Fawzi et al, 1993;Sommer et al, 1984;West et al, 1999). The main causes of vitamin A deficiency are inadequate intake of vitamin A-rich foods such as liver, full milk, butter, eggs, whole fish, green leafy vegetables and yellow-orange fruits, as well as increased requirements due to a high burden of infectious diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The ocular signs of VAD include night blindness, conjunctival xerosis, Bitot spots, corneal ulceration, keratomalacia and total blindness. Several studies have revealed that there is a positive association between VAD and increased respiratory infections (2,3) , diarrhoea, measles and childhood mortality (4)(5)(6)(7)(8)(9) . VAD compromises the immune system in 40 % of children in the developing world and contributes to one million deaths of young children each year (10,11) .…”
mentioning
confidence: 99%
“…According to Indonesia's national vitamin A survey in 1992, more than 50% of the under-®ve children had a marginal vitamin A status (Muhilal et al, 1994). Children with vitamin A de®ciency are at increased risk of blindness and death, and illness is generally more severe and lasts longer (Sommer et al, 1984;Beaton et al, 1993;Ghana VAST Study Team, 1993). Recently, a study in Nepal found that maternal mortality was reduced by 40 ± 50% when women were supplemented with a weekly low dose of vitamin A or b-carotene (West et al, 1999).…”
Section: Introductionmentioning
confidence: 99%